SQL clearly explained - Harrington, Jan L. (Morgan Kaufmann series in data management systems, 2010)
Although the core of the SQL language remains relatively unchanged, the most recent release of the SQL standard (SQL:2008) includes two sets of extensions: 1) support for object-relational databases and 2) support for XML. The second edition of this book included some material about the object-relational extensions. However, that set of commands has been greatly extended and the new edition takes that into account. The XML extensions are entirely new to the third edition. A chapter on basic relational concepts will be also added to broaden the audience and make the book more complete in its own right. All of the chapters will be revised to be sure they are up to date. Chapter 10 ("Views, Temporary Tables, and Indexes") from the second edition will be expanded to include common table expression (CTEs). The material in the existing Chapter 14 ("Unimplemented SQL-92 Features 251") will be disbursed through the chapters where the particular type of operation is discussed.